Pig Town Party - Cho, Lian (New York, NY : HarperCollins, 2024)
"Author-illustrator Lian Cho delivers a rib-tickling picture book about a young girl who receives a mysterious invite to a Pig Town party and follows the trail into a secret world of pigs--where epic parties, chase scenes, and a cake heist soon unfold. Hilarious twists abound!" --.
new kids book fall 2024.
Keywords: Pigs -- Juvenile fiction; Mistaken identity -- Juvenile fiction; Parties -- Juvenile fiction; Picture books